INVESTIGATION OF REVENUE SHARING, TRANSPARENCY AND FIRM PERFORMANCE TO PROFIT DISTRIBUTION MANAGEMENT - MISMIWATI MISMIWATI; TONA AURORA LUBIS; ENGGAR DIAH PUSPA ARUM (Management Department, Faculty of Economics and Business, Universitas Jambi, 2019)
This study was conducted to determine the effect on Profit Distribution Management recorded in Bank Indonesia on financing for profit sharing, transparency and performance. Research conducted using RGEC Method to determine the level of performance in the company and the population of this study is a company listed in the Jakarta Islamic Index of 2012-2016. The results of this study indicate that mudharabah variables have an effect but not significant to PDM, ROA and CAR have significant effect to PDM while musharaka, transparency, FDR, GCG and BOPO have no significant effect to PDM.